2012
DOI: 10.1523/jneurosci.1196-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Decreased Serotonin Release to the Antidyskinetic Effects of Deep Brain Stimulation in a Rodent Model of Tardive Dyskinesia: Comparison of the Subthalamic and Entopeduncular Nuclei

Abstract: Mechanisms whereby deep brain stimulation (DBS) of the subthalamic nucleus (STN) or internal globus pallidus (GPi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…These data provide proof-of-principle that nicotine exerts its effect via an interaction at nAChRs. Varenicline reduced VCMs to a greater extent than nicotine, a finding that may relate to varenicline’s ability to interact with 5-HT receptors (Creed-Carson, Oraha, & Nobrega, 2011; Creed, Hamani, Bridgman, Fletcher, & Nobrega, 2012; Lummis, Thompson, Bencherif, & Lester, 2011; Naidu & Kulkarni, 2001). …”
Section: Nicotine and The Nachr Agonist Varenicline Decrease Antipmentioning
confidence: 95%
“…These data provide proof-of-principle that nicotine exerts its effect via an interaction at nAChRs. Varenicline reduced VCMs to a greater extent than nicotine, a finding that may relate to varenicline’s ability to interact with 5-HT receptors (Creed-Carson, Oraha, & Nobrega, 2011; Creed, Hamani, Bridgman, Fletcher, & Nobrega, 2012; Lummis, Thompson, Bencherif, & Lester, 2011; Naidu & Kulkarni, 2001). …”
Section: Nicotine and The Nachr Agonist Varenicline Decrease Antipmentioning
confidence: 95%
“…Recently, renewed appreciation of serotonin's role in the motor and non‐motor symptoms of PD has stimulated research into the serotonergic effects of DBS treatment for movement disorders. In a haloperidol‐induced tardive dyskinesia rat model, STN‐DBS resulted in reduced serotonin release from the dorsolateral striatum, correlating with reduced dyskinetic movements in the animals (Creed et al , ). However, the same experiment found that when serotonin reduction is pharmacologically blocked, STN‐DBS was still able to rescue the phenotype, suggesting that several parallel therapeutic mechanisms are involved (Creed et al , ).…”
Section: Neurochemical Effectsmentioning
confidence: 99%
“…Treatment of hypokinetic disorder such as PD with 1220 STN-DBS may act by increase in GABA levels in the STN and 1221 thereby reduce the GABAergic GPi output to thalamus and 1222 strengthening thalamocortical facilitation, producing the clinical benefits (Feuerstein et al, 2011 GABA in the STN while the PD patients performed a memory task 1233 during surgery (Buchanan et al, 2014). Also, a study in 6-OHDA 1234 model of PD in mice (Yoon et al, 2014) (Creed 1260(Creed et al, 2012. Mood and cognition are also important non-motor 1261 features of PD (Emre et al, 2014).…”
Section: Dbs Acting Through Modulation Of Oscillationsmentioning
confidence: 99%
“…Mood and cognition are also important non-motor 1261 features of PD (Emre et al, 2014). In a rat model of tardive 1262 dyskinesia (Creed et al, 2012), STN-DBS decreased the activity of 1263 raphe neurons and thereby reduced serotonin levels, which 1264 produced the antidyskinetic effects. This decrease in serotonin 1265 levels has also been proposed as mechanism of depression in PD 1266 patients treated with STN-DBS (Creed et al, 2013) and GPi-DBS 1267 yielded a lower rate of depression than STN-DBS (Rodriguez-Oroz 1268.…”
Section: Dbs Acting Through Modulation Of Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation